Analysis of Publications Profile of Indian Mission-oriented R&D Sector - Gupta, B.M.; Dhawan, S.M. (DESIDOC Journal of Library & Information Technology, 2010)
The mission-oriented R&D sector covers institutions both under R&D agencies/departments and socio-economic ministries/departments of the Government of India. The paper describes the role and contribution of mission-oriented R&D in the overall research output of the country. The paper analyses various features of R&D sector such as its publications growth and output, impact of research, strong and week subject areas, collaboration profile, and major institutions and their quality. DOI: 10.14429/djlit.28.7.122